Effectiveness of community health management for hypertensive patients under the medical alliance in China: a systematic review and meta-analysis - Gu, Yi-Chun; Wang, An-Qi; He, Da; Tang, Chang-Hai (Frontiers in Public Health, 2025)
ObjectiveThe prevalence of hypertension in China has been increasing, imposing a heavy burden on premature mortality and catastrophic healthcare expenditure. This study aims to evaluate the effectiveness of community health management on blood pressure control for hypertensive patients under the medical alliance, a model of integrated care in China.MethodsFollowing PRISMA guidelines, three English databases and three Chinese databases were searched from January 2010 to March 2024, with two reviewers involved in the screening, data extraction, quality assessment, and narrative synthesis with characteristics and interventions. Meta-analysis was performed with the value of Hedge’s g and 95% confidence interval (CI), using the random-effects model. Subgroup and meta-regression analysis were used to analyze the sources of heterogeneity. Egger’s test was applied to detect publication bias.ResultsTwenty-five studies covering 7,727 hypertensive patients were included, with one of them assessed as low risk of bias. The pooled result showed that compared to conventional community health management, community health management of hypertension under the medical alliance had a more significant effect on reducing systolic blood pressure (Hedge’s g: −0.721, 95% CI: −0.890 to −0.552, p < 0.001) and diastolic blood pressure (Hedge’s g: −0.786, 95% CI: −1.002 to −0.571, p < 0.001). It could not be demonstrated that regional distribution, mean age of participants, sample size of the experimental group, sample size of the control group, duration of intervention, and publication year were the sources of heterogeneity. There was a significant publication bias in diastolic blood pressure.ConclusionThis study supports the effectiveness of community health management under the medical alliance in reducing blood pressure for hypertension. The guidance from general hospitals to community health centers, remote monitoring systems to expand the spatial scope of healthcare access and achieve information sharing, and two-way referral are efficient measures in the medical alliance.